Lattice Model of Intercalation - Mysakovych, T.S.; Krasnov, V.O.; Stasyuk, I.V. (Відділення фізики і астрономії НАН України, 2010)
The thermodynamics of a lattice model of intercalation of ions in crystals is considered in the mean-field approximation (MFA). The pseudospin formalism is used for the description of the interaction of electrons with ions, and the possibility of the hopping of intercalated ions between different positions is taken into account. Phase diagrams are built. It is shown that the effective interaction between intercalated ions can lead to the phase separation or the appearance of a modulated phase (it depends on the filling of the electron energy band). At high values of the parameter of ion transfer, the ionic subsystem can pass to the superfluid-like state. Дослiджено термодинамiку ґраткової моделi iнтеркаляцiї iонiв у кристали в наближеннi середнього поля. Для опису взаємодiї електронiв з iонами використано псевдоспiновий формалiзм та враховано можливiсть перескоку iонiв мiж вузлами ґратки. Побудовано фазовi дiаграми. Показано, що ефективна взаємодiя мiж iнтеркальованими iонами може приводити до роздiлення фаз або до появи модульованої фази (залежно вiд заповнення електронної енергетичної зони). При достатньо значнiй iнтенсивностi iонного переносу пiдсистема iонiв може перейти у стан, подiбний до надплинного. Исследована термодинамика решеточной модели интеркаляции ионов в кристаллы в приближении среднего поля. Для описания взаимодействия электронов с ионами использован псевдоспиновый формализм и принята во внимание возможность перескоков ионов между узлами решетки. Построены фазовые диаграммы. Показано, что эффективное взаимодействие между интеркалированными ионами может вызывать разделение фаз или приводить к появлению модулированной фазы (в зависимости от заполнения электронной зоны). При достаточно значительной интенсивности ионного переноса подсистема ионов может перейти в состояние, подобное сверхтекучему.